Welfare effects of social cash transfer programs : Evidence from Egypt$1 (Bs (3z(BTakaful(3y (Band (3z(BKaramah(3y (BPrograms /s - Hind Ibrahim Hanafy Mohammad; Sherine ElShawarby (2022)
(3JYJHQ GdJMhjdGJ GdfbOjI GdGLJeGYjI ChdhjI aj GdHdOGf GdCbd fehkG, MjK Jchf GdaLhI Hjf GdMGLI Edi GdMeGjI GdGLJeGYjI GdCSGSjI heG gh eJGM CcHQ(B. (3JeKd gPg GdOQGSI hGMOI ef Chdi GdOQGSGJ GdJj JJfGhd Jbjje GdBKGQ GdTGedI dHQfGeLj GdJMhjdGJ GdfbOjI GdGLJeGYjI yJcGady hycQGeIy aj eUQ(B. (3hJDcO GdfJGFL, GdeSJfOI Edi CSdhH GdJUeje ZjQ GdJLQjHj deWGHbI fbGW Gdejd (B(Propensity Score Matching (PSM)) (3hfgL GdGfMOGQGdeQLM (B(odds-weighted regression)(3, hHjGfGJ ef HMK GdONd hGdEfaGb hGdGSJgdGc (B2017-2018(3, GdBKGQ GdEjLGHjI dHQfGeLj GdJMhjdGJ GdfbOjI GdGLJeGYjI yJcGady hycQGeIy Ydi fUjH GdaQO ef fabGJ GdGSJgdGc ZjQ GdZPGFj HeG aj Pdc GdEfaGb Ydi GdQYGjI GdUMjI hGdJYdje ddCSQ GdeSJajOI(B. (3JTjQ GdfJGFL CjkVG Edi hLhO JCKjQGJ GdYJHI ddJMhjdGJ GdfbOjI GdGLJeGYjI ddHQfGeLjf, hGdJj JDKQ aj GdZGdH Ydi fabGJ GdQYGjI GdUMjI Hjf GdCSQ GdeSJajOI GdCcKQ abkQG aj GdCUhd hfabGJ GdJYdje Hjf GdeSJajOjf GdCcKQ KQGkA(B.s
Thesis (M.Sc.)-Cairo University-Faculty of Economics and Political Science,2022.
Bibliography: p. 118-133.
Keywords: Economics; Social cash transfers